2015
DOI: 10.1007/s00339-015-9208-y
|View full text |Cite
|
Sign up to set email alerts
|

A selector device based on graphene–oxide heterostructures for memristor crossbar applications

Abstract: Most of the potential applications of memristive devices adopt crossbar architecture for ultra-high density. One of the biggest challenges of the crossbar architecture is severe residue leakage current (sneak path) issue. A possible solution is introducing a selector device with strong nonlinear current-voltage (I-V) characteristics in series with each memristor in crossbar arrays. Here, we demonstrate a novel selector device based on grapheneoxide heterostructures, which successfully converts a typical linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Therefore, all parameters that are related to the bandgap will be changed by the bandgap energy such as, density of state (DOS), carrier concentration and conductance. 9 Also, these parameters in°uence the memristor's resistance switching and current-voltage characteristics by a direct tunneling model or a standard quantum tunneling equation as 14 ;…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, all parameters that are related to the bandgap will be changed by the bandgap energy such as, density of state (DOS), carrier concentration and conductance. 9 Also, these parameters in°uence the memristor's resistance switching and current-voltage characteristics by a direct tunneling model or a standard quantum tunneling equation as 14 ;…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinearity in the I – V results during positive bias suggested that the Ag/Melanin/SS memristive device is a highly nonlinear device. Such kind of nonlinearity is useful for the development of analog circuits, selector devices for crossbar memory application and chaotic circuits based on memristive devices. In addition to this, an anomalous negative differential resistance (NDR) effect is observed during the SET process, as shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, the endurance of a selector should be significantly greater than that of its series memristor because the selector is turned on for every programming and reading event. The tunneling barrier 37,38 and n–p–n 39 or p–n–p 40 junctions are commonly used in selectors. Ovonic threshold switching (OTS) behavior could also be used to achieve high nonlinearity for oxide capacitor devices; this requires the threshold resistive switching to occur transiently (less than 10 ns).…”
Section: Solutions To the Sneak Path Current Issuementioning
confidence: 99%